REPRESENTASI KEMISKINAN PADA TAYANGAN REALITY SHOW ORANG PINGGIRAN EPISODE BAKTI SUCI ANDIKA - Susanti, Nesa; Sari, Genny Gustina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Reality show with the theme of social and poverty in general the story of someone who lives in poverty and has shortcomings, both economically and physically. One reality show with the theme of social and poverty is a reality show episode edges of Consecrated Holy Andika. Episode BaktiAndika Holy featuring a boy struggles to support his family and also meet the needs of his brother without a father figure and only accompanied by a mother who has limitations in speaking and listening. This study was conducted to see how the reality show edges pack a phenomenon and poverty explain denotation, connotation and myth then shown again on the outskirts of the reality show episode Holy BaktiAndika.This study uses qualitative descriptive analysis technique semiotics of Roland Barthes. The object of research is the video display program outskirts of the reality show episode Holy BaktiAndika with a duration of 21 minutes 1 second that aired on January 17, 2016.The results of this study indicate that: (1) The meaning of denotation poverty on impressions Suburb People accentuate poverty as a condition identical to the material shortages and the inability to meet the physical needs of everyday. (2) The meaning connotation indicates that in general the poor, who work for a living is not only done by the head of the family, but the whole family, including children. (3) The myth that developed in the community that poverty is a form of structural poverty (caused by human activity), such as the lack of facilities of an area as well as the inequality of local communities with urban communities, as well as poor people are considered to have the attitude of surrender or accept things as they are and resignation this associated with traditional cultural society.Keyword: semiotic analysis, Reality Show, Proverty.